La ronda campesina en una comunidad campesina en el norte del Perú: La Toma en Cajamarca - Korsbaek, Leif (2008)
The article analyzes the Rondas campesinas as a self-defense institution created by indigenous and Mestizo peasant communities of highland Peru. The case study is the Rondas of the rural highland community of La Toma, located in Cajamarca, northern Peru. Rondas campesinas were created during the 1970s to prevent aggressions both from the State and from private landowners to communal lands and other property in a context of the agrarian reform in force then. In addition, the Rondas served as a powerful institution during the internal war against Sendero Luminoso from 1980 through the 1990s. In such processes, the Rondas of La Toma proved to be a really representative institution of the rights of its community and this is the hypothesis this article demonstrate.